IMPLEMENTASI LOCATION BASED SERVICE PADA APLIKASI HALO TAMBAL BAN BERBASIS ANDROID DI KOTA MALANG - Balandra, Daniel Dwi; Sujito, Sujito; Primandari, Liduina Asih (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2019)
Leaks on vehicle tires experienced by motorists, and become an obstacle to vehicles when traveling, require motorists to push their vehicles to avoid excessive damage to the tires. In finding a tire service provider to fix tire leakage problems, sometimes the driver must push the vehicle without knowing where and how far to find a tire repair service provider. The HALO Tambal Ban application is an application that provides information about tire patch service providers. Application built to facilitate finding information about tire patch service providers, information about location, availability of services, operating hours, to tariffs imposed by tire patch service providers. To obtain information about the location of the nearest tire repair service provider from the application user, this research proposes to implement the Location Based Service feature on the HALO Tambal Ban application, to obtain more accurate location information. Using HTML5 and AngularJS programming languages, Ionic as a Framework, and firebase as database processing. In order to improve the accuracy of location data obtained by the application by implementing the Location Based Service feature on the HALO Tambal Ban application. Keywords: Tambal Ban, Android, Ionic, Location Based Service, Malang